Catechol-O-methyltransferase (COMT) Val158Met Polymorphism and Prepulse Inhibition of the Change-related Cerebral Response. (July 2022) - Motomura, Eishi; Tanii, Hisashi; Kawano, Yasuhiro; Inui, Koji; Okada, Motohiro
Highlights: COMT genotype influenced the prepulse inhibition (PPI) of change-related response. The %PPI in Met carriers was greater than that in Val/Val healthy individuals. This index has the potential to be an endophenotype of schizophrenia. Abstract: Change-related potentials elicited by an abrupt sound feature's change are attenuated by a leading weak sound (prepulse inhibition: PPI). We investigated whether the PPI index is associated with the catechol-methyltransferase (COMT) Val158Met polymorphism (rs4680), which is involved in the metabolism of dopamine in the prefrontal cortex. Healthy subjects with normal hearing were recruited ( n  = 70). A train of 100-Hz clicks 650 ms in duration was used. The test stimulus was an abrupt increase in sound intensity (+10 dB) from the baseline (70 dB) provided at 400 ms after the sound onset. Three consecutive clicks at 30, 40, and 50 ms before the change's onset were greater (+3 or +5 dB) from the baseline as a prepulse. The targeting auditory evoked potential component was Change-N1 peaking approx. 130 ms after the change onset. We calculated the inhibition level as the% inhibition of the Change-N1 amplitude by a prepulse. The %PPI in the Met-carriers was significantly greater than that in the Val/Val-individuals. Our results suggest that dopamine might play a role in the PPI of the change-related response. We propose that this index has the potential to identify an intermediate phenotype in psychiatric disorders such as schizophrenia.